2021
DOI: 10.1186/s12859-021-04401-3
|View full text |Cite
|
Sign up to set email alerts
|

Laniakea@ReCaS: exploring the potential of customisable Galaxy on-demand instances as a cloud-based service

Abstract: Background Improving the availability and usability of data and analytical tools is a critical precondition for further advancing modern biological and biomedical research. For instance, one of the many ramifications of the COVID-19 global pandemic has been to make even more evident the importance of having bioinformatics tools and data readily actionable by researchers through convenient access points and supported by adequate IT infrastructures. One of the most successful efforts in improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…While HEV testing is typically performed in the liver, we tested the muscle tissue because it is more suitable from a food safety perspective. Furthermore, previous studies conducted in Italy reported a prevalence of 1.35% and 5.6% in wild boar muscle [18] and muscle and liver [33], respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While HEV testing is typically performed in the liver, we tested the muscle tissue because it is more suitable from a food safety perspective. Furthermore, previous studies conducted in Italy reported a prevalence of 1.35% and 5.6% in wild boar muscle [18] and muscle and liver [33], respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Bioinformatic analysis was performed using the Galaxy interface [32,33]. The raw reads were trimmed using Trimmomatic 0.38 [34] for removing Nextera adaptors and other Illumina-specific sequences (Illuminaclip set to Nextera (paired-ended)), removing low-quality residues at the start and the end of the reads (leading:10 and trailing:10), clipping reads when the average Q-scores dropped below 20 over a sliding window of four residues (sliding window, 4:20), and dropping reads shorter than 40 bases after processing (minlen, 40).…”
Section: Data Analysis Of Whole Genome Sequencing (Wgs)mentioning
confidence: 99%
“…All the bioinformatic analyses were performed using the tools on the Staphylococcus aureus Intensive Server for Research in Omics data (SIRIO) Galaxy instance ( accessed on 1 August 2023): an online user-friendly Galaxy interface for performing raw read trimming, assembly, and SE gene detection [ 30 , 31 ]. The raw reads were trimmed using Trimmomatic 0.38 [ 32 ] by removing the Nextera adaptors and other Illumina-specific sequences (Illuminaclip set to Nextera (paired-ended)), by removing low-quality residues at the start and the end of the reads (leading:10 and trailing:10), by clipping the reads when the average Q-scores dropped below 20 over a sliding window of four residues (slidingwindow:4:20), and by dropping the reads shorter than 40 bases after processing (minlen:40).…”
Section: Methodsmentioning
confidence: 99%
“…All bioinformatic analyses were performed with the tools on the Galaxy instance S.I.R.IO. http://90.147.102.165/galaxy, an online user-friendly Galaxy interface for performing bacterial genome analyses [28][29][30]. The raw reads were trimmed using Trimmomatic 0.38, by removing Nextera adaptors and other Illumina-specific sequences (Illuminaclip set to Nextera, paired-ended), by removing low-quality residues at the start and the end of the reads (leading:10 and trailing:10), by clipping reads when the average Q-scores dropped below 20 over a sliding window of four residues (slidingwindow:4:20) and by dropping reads shorter than 40 bases after processing (minlen:40) [31].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%